Erratum - Editor, (Archives of Rheumatology, 2014)
We regret that the author's names were not printed in the correct order in the article by Heng et al. titled “Is There a Bridge Between Systemic Lupus Erythematosus and Thymomas” which appeared in the Turkish Journal of Rheumatology 2013;28(4):267–270. The order of the authors' names should now read as follows: Yin Heng2, Tao Ye2, Chen Xi1, Yin Geng1, Xie Qibing1.